Ingmar Bergman : An enduring legacy - Hedling, Erik; Hedling, Erik (Lund Lund University Press, 2021)
This book on Swedish filmmaker Ingmar Bergman contains eighteen new scholarly chapters on the director$1 (Bs work, mainly in the cinema. Most of the contributors$1 (Bsome Swedish, others American or British$1 (Bhave written extensively on Bergman before, some for decades. Bergman is one of the most written-about artists in film history and his fame still lingers all over the world, as was seen in the celebrations of his centenary in 2018. The book was specifically conceived at that time with the aim of presenting fresh angles on his work, although several chapters also focus on traditional aspects of Bergman$1 (Bs art, such as philosophy and psychology. Ingmar Bergman: An Enduring Legacy thus addresses a number of essential topics which have not featured in Bergman studies before, such as the director$1 (Bs relations with Hollywood and transnational film production. It also deals at length with Bergman$1 (Bs highly sophisticated use of film music and with his prominence as a writer of autobiographical literature, as well as with the intermedial relations to his films that this perspective inevitably entails. Finally, the book addresses Bergman$1 (Bs complex relations to Swedish politics. Many different approaches and methods are employed in the book in order to show that Bergman remains a relevant and important artist. The analyses generally focus on some of his most memorable films, like Smiles of a Summer Night, The Seventh Seal, Wild Strawberries, Persona, and Fanny and Alexander; but some rarer material, including Hour of the Wolf, The Lie, and Autumn Sonata, is discussed as well.s
English
Keywords: Films, cinema; Film theory & criticism; Individual film directors, film-makers; Ingmar Bergman; Swedish cinema; film criticism; Erik Nordgren; transnational film production; Henrik Ibsen; Arthur Janov; film music; autobiographical writing; auteurism